2000
DOI: 10.1034/j.1399-3070.2000.00133.x
|View full text |Cite
|
Sign up to set email alerts
|

Waste recycling in Malaysia: problems and prospects

Abstract: Recycling of solid wastes should be integrated into the existing and future waste management plans so as to yield the benefits of conservation of natural resources, saving of fossil fuels and prolonging lifespan times of disposal sites. This paper discusses the current status of waste recycling in Malaysia and its future prospects. Although a large amount of Malaysian wastes could be recycled, less than 5% of the total (almost 10 000 t d‐1) is actually separated and recycled. There is a good demand for waste p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…The success of 3R policy is mainly depending on effective public involvement. The appropriate knowledge of separation of waste can reduce collection time and cost (Hassan & Rahman, 2000). In fact, public awareness and attitudes towards recycling are the most influencing factors for recycling program in the context of most developing nations (Troschinetz & Mihelcic, 2009).…”
Section: Attitudes Towards Environmental Issuesmentioning
confidence: 99%
“…The success of 3R policy is mainly depending on effective public involvement. The appropriate knowledge of separation of waste can reduce collection time and cost (Hassan & Rahman, 2000). In fact, public awareness and attitudes towards recycling are the most influencing factors for recycling program in the context of most developing nations (Troschinetz & Mihelcic, 2009).…”
Section: Attitudes Towards Environmental Issuesmentioning
confidence: 99%
“…The budget for waste collection was ranging from 20% to 70%, according to the size of the municipality (Hassan et al 2000). Dumping of wastes in open fields and rivers are common even until today and a study of waste disposal behaviour in Kuala Lumpur indicated that 31.9% of waste were disposed by open burning, while 6.5% were dumped into the river system (Murad & Siwar 2007).Hence the environmental safety concern in Malaysia was secondary and most municipalities had a tough time in finding new disposal sites as, the existing disposal sites were nearly exhausted (Hassan et al 2000). Kuala Lumpur, is on dire need to reduce its dependence on landfills due to its population density and an alternative solution such as incinerator is difficult to implement.…”
Section: Integrated Solid Waste Management -Problems and Issuesmentioning
confidence: 99%
“…In Malaysia, waste minimization programs cannot be carried out effectively without a reliable data on waste composition and generation (Hassan et al 2000)1. The amount of Malaysian solid waste being separated at source for recycling purposes was less than 2% in the year 1992 but the senior government officials believe that the actual rate could be as high as 15%.…”
Section: Waste Minimization Resource Recovery and Climate Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the greatest challenge is to provide more waste disposal facilities such as landfill to treat the waste (Hassan et al, 2001). Despite the complexity of waste produced, the standards of landfills in most developing countries are still poor; these include inadequate waste treatment facilities, inefficient collection and storage systems, co-disposal of municipal waste with hazardous waste, inefficient utilisation of disposal space, lack of environmental abatement measures and poor documentation (Hassan et al, 2000). As a consequence, a great deal of contamination, especially to surface water, soil and ground water, occurs, threatening the health of exposed populations and ecosystems (Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%